2014
DOI: 10.5007/2175-7925.2014v27n3p149
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos anátomo-radiográficos e tempo de trânsito gastrintestinal em jacaré tinga Caiman crocodilus crocodilus (Linnaeus, 1758) (Crocodylia, Alligatoridae)

Abstract: Resumo O interesse pela criação de jacarés em cativeiro tem aumentado no Brasil, no entanto, faltam estudos aprofundados sobre o tipo e a frequência de alimentação adequada destes répteis em cativeiro. Objetivou-se determinar os aspectos an tomo-radio r cos e o tempo de trânsito astrintestinal do Caiman crocodilus crocodilus por meio de radio ra as contrastadas. Os de jacarés, cinco machos e cinco fêmeas, foram contidos sicamente para a administração, via sonda oro strica, de 0 ml/ de suspensão de sulfato de b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…In the species analyzed in this study, Boa constrictor amarali, the mean gastrointestinal transit time (recorded until the complete emptying of the small intestine) was longer (97±15.65 hours) when compared to the Python regius (48±15.17 hours) studied by Banzato et al (2012). In addition, it was longer than in the Caiman crocodiles crocodilus, mean 74.8±22.8 hours (Pereira et al, 2014), in the Iguana iguana, mean 16 hours (Smith;Dobson;Speen, 2001), and in the Trachemys dorbignyi and Trachemys scripta elegans, mean 3.47 days (Moraes, 2007).These descriptions demonstrate the importance of studies on different species, as there are interspecific peculiarities.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In the species analyzed in this study, Boa constrictor amarali, the mean gastrointestinal transit time (recorded until the complete emptying of the small intestine) was longer (97±15.65 hours) when compared to the Python regius (48±15.17 hours) studied by Banzato et al (2012). In addition, it was longer than in the Caiman crocodiles crocodilus, mean 74.8±22.8 hours (Pereira et al, 2014), in the Iguana iguana, mean 16 hours (Smith;Dobson;Speen, 2001), and in the Trachemys dorbignyi and Trachemys scripta elegans, mean 3.47 days (Moraes, 2007).These descriptions demonstrate the importance of studies on different species, as there are interspecific peculiarities.…”
Section: Discussionmentioning
confidence: 68%
“…The 25mL/kg dose was also determined based on that same study, as it took into consideration the great extension capacity of the gastrointestinal tract in serpents. However, other gastrointestinal transit studies on reptiles found in the literature used lower doses of barium sulfate, in animals such as Testudines (Lopes, 2006;Moraes, 2007) and in Caiman crocodiles crocodiles (Pereira et al, 2014). Those studies used a 10mL/kg dose of barium sulfate associated with mineral oil.…”
Section: Discussionmentioning
confidence: 99%